Factores que inciden en la Seguridad de la Información en las Organizaciones - Rodriguez-Barrantes, Samir B. (2024)
It is validated in this research paper that cybercrime has increased from 415 to 463 million people victim of this type of delinquency despite diverse studies, regulations and recommendations, frameworks, among others. Therefore, it is important to identify the factors that affect information security. The current paper is a basic research, since it will increase theoretical knowledge regarding data safety, and it also has a qualitative approach using interviews based on local Peruvian reality focused on the perspectives held by the Chief Information Officer and Chief Security Officer. At the end of it, the factors identified that affect information security: technological, human, regulatory and communication related.